The Influence Of Brand Image On The Decision To Use Maxim Services In Bengkulu City - Putra, David Mandala; Sari, Sapta; Maryaningsih, Maryaningsih (Journal of Law, Social Science, and Management Review, 2025)
This study aims to analyze the influence of brand image on the decision to use Maxim's services in Bengkulu City. A quantitative survey method was employed, involving 100 randomly selected Maxim users. The research instrument, in the form of a questionnaire, was tested for validity and reliability. Classical assumption tests confirmed that the data met the requirements of normality, homoscedasticity, and linearity. The simple linear regression analysis showed that brand image had a positive and significant effect on the decision to use Maxim’s services, with a regression coefficient of 0.404 and a significance level of p = 0.000 (p < 0.05). The coefficient of determination (R²) was 0.247, indicating that brand image accounted for 24.7% of the variance in usage decisions, while the remaining 75.3% was influenced by other factors outside the model. These results suggest that a more favorable brand image leads to a higher likelihood of consumers choosing Maxim's services. Aligned with Brand Equity theory, the findings emphasize the importance of consumer perception in shaping decisions. Practically, it implies that Maxim should continue to strengthen its brand identity, improve service quality, and enhance user experience to maintain and increase customer engagement.